The Duration of the Adjustment Process of Financial Ratios - Peles, Yoram C.; Schneller, Meir I. (The Review of Economics and Statistics, 1989)
Are financial ratios an observed quantity that is influenced by firms or capital and product markets? The current body of empirical research concentrates on the time series behavior of such ratios when corporate distress is revealed. In this study the time series properties of joint-concern firms is examined. It is shown that for six financial ratios under examination, the data are consistent with partial adjustment process with finite adjustment durations. These durations are estimated through a methodology that does not require an a priori knowledge of the level toward which ratios are adjusted. Furthermore, the order of the six discerned durations is consistent with common wisdom. Copyright 1989 by MIT Press.